THEORETICAL CONTENT OF HUMAN CAPITAL AND ITS COMPOSITION - Bondarchuk, N.V. (The actual problems of regional economy development, 2018)
The article is devoted to the study of the theoretical content of human capital and its main components. The purpose of the study is to determine the theoretical content of the concept of «human capital» as an object of accounting and its components. It is established that the central place in the process of transition to the knowledge economy is given to a person who should have high creative potential, to be a highly skilled professional. According to its professionalism, the results of intellectual, innovative activity and success in an innovative economy depend accordingly. It was discovered the main definitions of “human capital” in the writings of economists. It is stated that man and his productive abilities occupy a central place in psychological, pedagogical and socio-economic sciences. Differences in the interpretation of this definition depend on: first, the separation of the components of human capital (capital of health, intellectual capital, mobility, motivation, culture, creative abilities, talent, upbringing, mentality, adaptability); - secondly, in the sphere of human capital use (economic, social, psychological, pedagogical, managerial, accounting category). To form a complete understanding of the essence, features of human capital and its significance in various spheres of business entities substantially disclosed elements of the category under investigation. The main components of human capital are identified: capital of health, intellectual capital, mobility, motivation, culture, creative abilities, talent, education, mentality, adaptability). In the course of the research, the functions of each component of human capital are specified. The main areas of further research are the specification of the accounting principles and procedures of the human capital, the formation of common methodological approaches in the methods of assessment of human capital.